The complete chloroplast genome of Pedicularis alaschanica (Orobanchaceae). Issue 2 (3rd July 2019) - Wu, Chenyu; Fang, Dongming; Wei, Jinpu; Wang, Xuebing; Chen, Xiaoli
Abstract: The complete chloroplast genome sequence of Pedicularis alaschanica was determined and described. The complete chloroplast was 146, 989 bp in length with typical quadripartite structure and overall GC content of 38.4%, which encompassed 68 protein-coding genes, 22 tRNAs, 4 rRNAs, and 11 pseudogenes. The functions of ndh genes were lost. The phylogenetic analysis indicated that P. alaschanica was close to other species of Pedicularis . This study would contribute to enrich the Pedicularis chloroplast genome resource and promote the biological research.